Machining of glass fiber reinforced polyamide (eXPRESS Polymer Letters)
The machinability of a 30 wt% glass fiber reinforced polyamide (PA) was investigated by means of drilling tests. A disk was cut from an extruded rod and drilled on the flat surface: thrust was acquired during drilling at different drilling speed, feed rate and drill diameter. Differential scanning calorimetry (DSC) and indentation were used to characterize PA so as to evaluate the intrinsic lack of homogeneity of the extruded material. In conclusion, it was observed that the chip formation mechanism affects the thrust dependence on the machining parameters. A traditional modeling approach is able to predict thrust only in presence of a continuous chip. In some conditions, thrust increases as drilling speed increases and feed rate decreases; this evidence suggests not to consider the general scientific approach which deals the machining of plastics in analogy with metals. Moreover, the thrust can be significantly affected by the workpiece fabrication effect, as well as by the machining parameters; therefore, the fabrication effect is not negligible in the definition of an optimum for the machining process.